Formation of hierarchical bone-like apatites on silk microfiber templates via biomineralization. Issue 80 (12th August 2016) - Xu, Zongpu; Shi, Liyang; Hu, Doudou; Hu, Binhui; Yang, Mingying; Zhu, Liangjun
Abstract : Hierarchical bone-like apatites can be formed on silk microfiber templates and the resulting biocomposites achieved good cytocompatibility. Abstract : Silk microfibers (mSF) are attractive in tissue engineering because of their good plasticity and significant mechanical reinforcement effect. Bone-like apatites coated on the surface of mSF through biomineralization have been rarely reported. In this study, mSF with lengths of 200–300 μm were prepared and used as templates for biomineralization. By immersing in 1.5 times stimulated body fluid (1.5 × SBF), a hierarchical bone-like apatite layer can be formed on the surface of the mSF, which was developed in a time-dependent manner. As basic units, hydroxyapatite (HAp) nanoplates will assembly into microspheres with sophisticated flower-like structures and then, the microspheres gradually aggregated into a complete mineral layer overcovering the mSF. Multiple methods were used to characterize and analyze the organic/inorganic composites, including their morphology, structural and crystallographic properties, as well as the interface between the two different phases. The template effect of the mSF in the biomineralization process was investigated and a possible mechanism was proposed. In addition, cytocompatibility evaluation showed the mineralized silk microfibers (mmSF) tended to achieve better outcomes for cell growth and proliferation. This work provides a facile approach towards the development of mSF/HAp biocomposites, which possess potential applications in bone tissue engineering.